Herbivore dunging and endozoochorous seed deposition in a Mediterranean dehesa - Malo, J. E.; Jimenez, B.; Suarez, F. (JOURNAL OF RANGE MANAGEMENT, 2000)
Spatial patterns of herbivore defecation within grazing systems are important as they directly affect pasture growth and composition. These effects are partially linked to seed dispersal in dung, a little studied process. This paper focuses on: (1) quantification of dung and seeds deposited by herbivores in a Mediterranean grazing system, and (ii) analysis of the spatial variability of dung and seeds deposited within and among plant communities. We carried out year-long monthly quantifications of the depositions of rabbit (Oryctolagus cuniculus), fallow deer (Dama dama), red deer (Cervus elaphus), and cow (Bos taurus) dung to 32 plots distributed in Quercus rotundifolia Lam. and Fraxinus angustifolia Vahl woodlands, mixed scrub, and Cistus ladanifer L. scrub. We also quantified the germinable seed content of dung. The results revealed differences (p < 0.05) in dung deposition, varying (i) among the 4 species, (ii) within species (except for the red deer) among plant communities, and (iii) within plant communities. An average of 735 seeds/m(2) were returned to the soil via dung, with the highest numbers in open woodlands (870-1,888 seeds/m(2)) and the lowest numbers in scrubs (83-315 seeds/m(2)). Cows dispersed the most seeds (68%), followed by red deer (20%), rabbits (7%), and fallow deer (5%). Spatial variability in deposition led to accumulations of up to several thousand seeds at points covered by the dung. The effect of seed input to the seed bank and on vegetation may be low at large and medium-sized spatial scales, but it can be very important at small scales and for colonization processes.
The following values have no corresponding Zotero field: pub-location: 445 UNION BLVD, STE 230, LAKEWOOD, CO 80228-1259 USA publisher: SOC RANGE MANAGEMENT
Keywords: dispersal; dung; endozoochory; herbivores; Mediterranean pastures; Spatial pattern

Herbivore dunging and endozoochorous seed deposition in a Mediterranean dehesa - Malo, J E; Jimenez, B; Suarez, F (JOURNAL OF RANGE MANAGEMENT, 2000)
Spatial patterns of herbivore defecation within grazing systems are important as they directly affect pasture growth and composition. These effects are partially linked to seed dispersal in dung, a little studied process. This paper focuses on: (1) quantification of dung and seeds deposited by herbivores in a Mediterranean grazing system, and (ii) analysis of the spatial variability of dung and seeds deposited within and among plant communities. We carried out year-long monthly quantifications of the depositions of rabbit (Oryctolagus cuniculus), fallow deer (Dama dama), red deer (Cervus elaphus), and cow (Bos taurus) dung to 32 plots distributed in Quercus rotundifolia Lam. and Fraxinus angustifolia Vahl woodlands, mixed scrub, and Cistus ladanifer L. scrub. We also quantified the germinable seed content of dung. The results revealed differences (p < 0.05) in dung deposition, varying (i) among the 4 species, (ii) within species (except for the red deer) among plant communities, and (iii) within plant communities. An average of 735 seeds/m(2) were returned to the soil via dung, with the highest numbers in open woodlands (870-1,888 seeds/m(2)) and the lowest numbers in scrubs (83-315 seeds/m(2)). Cows dispersed the most seeds (68%), followed by red deer (20%), rabbits (7%), and fallow deer (5%). Spatial variability in deposition led to accumulations of up to several thousand seeds at points covered by the dung. The effect of seed input to the seed bank and on vegetation may be low at large and medium-sized spatial scales, but it can be very important at small scales and for colonization processes.
Keywords: dispersal; dung; endozoochory; herbivores; Mediterranean pastures; Spatial pattern

The dispersal of a dry-fruited shrub by red deer in a Mediterranean ecosystem - Malo, Juan E; Suárez, Francisco (Ecography, 1998)
Seed dispersal of dry-fruited shrubs has received little attention in Mediterranean areas despite their frequency in the vegetation and the consideration given to the dispersal of fleshy-fruited shrubs in the area. Red deer faeces has recently been found to contain large numbers of seeds from one of the most common shrubs of this group, gum cistus Cistus ladanifer, although its importance in the reproduction of the species is unknown. This study examines the role of the red deer as an effective disperser of C. ladanifer. For this purpose, we quantify i) the C. ladanifer seed content in red deer dung over a year, ii) the seed shadow generated by the red deer wish their faeces during the same period, and iii) the ability of the dung-borne seeds to germinate and establish as seedlings under field conditions within five years following excretion. The results reveal an extremely high seed Content of the species in red deer dung (up to 80.5 ± 41.9 germinable seeds g-1), which is virtually confined to the summer (July–August), when we estimate that a red deer defecates up to 24 000 seeds of the species per day. Furthermore, red deer mainly deposit gum cistus seeds amongst plant formations lacking the species: over the year, red deer excrete <2600 seeds m-2 in C. ladanifer-dominated scrub and 7400–8800 seeds m-2 in other plant formations. Under natural conditions, the dung-borne seeds have a more sniggered among-years germination pattern than free seeds in the soil. Though no seedling survived its first summer drought, the survival of seedlings sprouted from dung was significantly longer than that of control seedlings in the first and third years after deposition, and indistinguishable from it the second, fourth and fifth years. This is the first quantification of the importance of red deer to C. ladanifer dispersal and establishment, and suggests that endozoochory by mammalian herbivores can be very valuable for dry-fruited shrubs in the Mediterranean region.
Keywords: endozoochory; red deer; seed dispersal; seedling establishment (PG)

The dispersal of a dry-fruited shrub by red deer in a Mediterranean ecosystem - Malo, Juan E.; Suárez, Francisco (Ecography, 1998)
Seed dispersal of dry-fruited shrubs has received little attention in Mediterranean areas despite their frequency in the vegetation and the consideration given to the dispersal of fleshy-fruited shrubs in the area. Red deer faeces has recently been found to contain large numbers of seeds from one of the most common shrubs of this group, gum cistus Cistus ladanifer, although its importance in the reproduction of the species is unknown. This study examines the role of the red deer as an effective disperser of C. ladanifer. For this purpose, we quantify i) the C. ladanifer seed content in red deer dung over a year, ii) the seed shadow generated by the red deer wish their faeces during the same period, and iii) the ability of the dung-borne seeds to germinate and establish as seedlings under field conditions within five years following excretion. The results reveal an extremely high seed Content of the species in red deer dung (up to 80.5 ± 41.9 germinable seeds g-1), which is virtually confined to the summer (July–August), when we estimate that a red deer defecates up to 24 000 seeds of the species per day. Furthermore, red deer mainly deposit gum cistus seeds amongst plant formations lacking the species: over the year, red deer excrete <2600 seeds m-2 in C. ladanifer-dominated scrub and 7400–8800 seeds m-2 in other plant formations. Under natural conditions, the dung-borne seeds have a more sniggered among-years germination pattern than free seeds in the soil. Though no seedling survived its first summer drought, the survival of seedlings sprouted from dung was significantly longer than that of control seedlings in the first and third years after deposition, and indistinguishable from it the second, fourth and fifth years. This is the first quantification of the importance of red deer to C. ladanifer dispersal and establishment, and suggests that endozoochory by mammalian herbivores can be very valuable for dry-fruited shrubs in the Mediterranean region.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: endozoochory; red deer; seed dispersal; seedling establishment (PG)

Herbivorous mammals as seed dispersers in a Mediterranean dehesa - Malo, Juan E; Suárez, Francisco (Oecologia, 1995)
Endozoochorous seed dispersal by herbivo- rous mammals has been verified repeatedly and its possi- ble influence on the structure and function of herbaceous communities has been suggested. Quantitative studies, however, are lacking in the field of seed dispersal via the dung of herbivore guilds in little-altered environments. The present paper analyses seed dispersal via rabbit, fal- low deer, red deer and cow dung in a Mediterranean de- hesa (open woodland used for hunting and ranching) during the seeding season. Dung seed content was deter- mined by the glasshouse cultivation of eight dung sam- ples from each herbivore, collected fortnightly between February and August. The four herbivores disperse many seeds (spring averages are 6-15 seeds per gram of dry dung and maxima of 25-70) from a large number of spe- cies (totals between 52 and 78). Dispersal seems to be mainly determined by seed production of the plant com- munity. This is reflected in (i) the dissemination of a high percentage of the species present in the dehesa, (ii) great seasonal variability, related to seed production, in the amount of seeds and number of species dispersed, and (iii) a high semi-quantitative similarity of seed con- tent in the four types of herbivore dung throughout the year. There is also important quantitative variation that depends on animal traits and feeding habits. These re- sults and the characteristics of species found in dung suggest the adaptation of plant species to the dispersal of their seeds via herbivore gut. This process may well have profound implications for vegetation dynamics and the evolution of plant traits.
Keywords: endozoochory; mediterranean grasslands; pasture dynamics; seed dispersal; Therophytes